GEGURITAN SALAMPAH LAKU DALAM PANDANGAN STILISTIKA - I Nyoman Suka Ardiyasa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Stylistics is the science of using language in literary works. Use of language stylesspecifically in literature. The language style that arises when the author expresses his idea. Thisstyle of language is an art effect and is influenced by conscience. Through this style of languagea poet expresses his idea. Disclosure of ideas created through beauty in the author's languagestyle. In Geguritan Salampahlaku The work of Ida Made Sidemen Geguritan Salampah Laku isa composition of Bali Purwa poetry whose choice of words has been precisely and carefullydetermined by the poet (Ida Pedanda Made Sidemen), so that both the title and lyrics in theverses are heard as a unified whole and attracts the audience to explore deeper into the contentsof the geguritan. This Geguritan tells the life journey of an Ida Pedanda Made Sidemen. Throughthe stories arranged array where the poet appears to create cohesive meaning from the beginningto the end through concrete words. The concrete arrangement as a whole tells how Ida PedandaMade Sidemen's life journey is full of simplicity. Geguritan Salampah Laku is also a literarywork that is very rich in plastic language (Figurative Language) where the figure of an IdaPedanda Made Sidemen who is very humble, can be seen in the use of majas-majas litotes whichalways declares his deficiencies and does not want to glorify himself. Poets are also very concernedabout the pattern of taxation that was built by the pupuh-upuh which is certainly bound by therules of padalingsa, the teacher of wilang, and the master teacher. The tone conveyed is aphilosophical tone that appears from the poets' life philosophies as outlined in the literary work.In Geguritan Salampah Laku the Poet implies a moral message as an opening, that is, in thislife, don't ever glorify yourself or boast.Keywords: Geguritan Salampah Laku, Stylistics